A Review: Bhutanese perspective of Community Vitality - Tandin Wangdi (Indonesian Journal of Education and Social Sciences, 2022)
The decline in community vitality and its concern are lately discussed social issue worldwide. Bhutan is no exception. This study aimed at evaluating the concept of community vitality as a tool to assess the impact of economic development on social capital in rural and urban communities in Bhutan. The literature review in the field of community vitality was employed in this research to achieve the aim of the study. The study concluded that a paradigm shift based on social transformation, rather than technology, was observed urgently needed globally to tackle unsustainable and unhappy societies associated with global problems. Moreover, the study revealed that the rural people of Bhutan trust more in neighbors, share stronger family relationships, are safe from violence, donates time and money to community activities, and do more volunteering services comparing to those who live in an urban area.